Latency Aware and Resource-Efficient Bin Pack Autoscaling for Distributed Event Queues: Parameters Impact and Setting - Ezzeddine, Mazen; Baude, Françoise; Huet, Fabrice; Laaziz, Fatima (SN computer science, 2025)
The event driven architectural style is becoming increasingly popular for designing large scale real time cloud applications. In this architectural style, an application is composed of a set of services that communicate by exchanging events over a distributed event queue rather than over remote procedure calls RPC. To achieve real time processing, services (event consumers) in the application must be able to consume and process events in less than a desired latency. Meeting such desired latency must be accomplished at low cost in terms of resources used. This paper presents a new approach to dynamic event consumer provisioning in distributed event queues, focusing on latency-awareness and resource efficiency. Our proposed solution models the dynamic event consumer replica provisioner as a two-dimensional bin packing problem. Furthermore, we discuss how dynamic event consumers provisioning in distributed event queues necessitates a blocking synchronization protocol that is at conflict with meeting a desired latency for high percentile of events. To address this issue, we propose an extension to the bin pack autoscaler logic to reduce the tail latency caused by the events accumulated during the blocking synchronization protocol. As part of the experimental work, we provide insights and recommendations on the configuration of the proposed bin pack model when the events processing time and the workload feature large variance.